Design of Digital up Converter for Solid-State Transmitters - Mertle Pinto, Lenisha; Hameed V, Shahul; Veena Devi Shastrimath V, Dr; ., . (International Journal of Engineering and Technology, 2018)
Digital Up converters (DUC) are used in communication system for the baseband processing and it is implemented in solid-state transmitters. The design of DUC is the most significant block in every digital communication system. The input signal applied that has to be upsampled and mixed with the carrier signal that is generated from Direct Digital Synthesizer (DDS). In this work processing is done using filters like Cascaded Integrator Comb (CIC), Compensator-FIR (CFIR), Pulse-Shaping Finite Impulse Response (PFIR), Half Band Filters (HBF) and Finite Impulse Response (FIR) filters are being used as interpolation filters. It is also explained that HBFâ€™s are preferable over CIC filters. This paper focuses on effective implementation of the DUC in order to reduce the resources for the optimisation of the design. Â Â